Сlassification description and exercise system in training foreign students a speciality language (levels A2  B1, B1+) - Дубинина, Л.; Манивская, Т. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2019)
Existing systems of exercises on the communicative competence formation of foreign students, learning Russian, have been considered in this article. Different approaches to the exercise classification system have been suggested. A new approach to the selection and presentation of basic learning tools (exercises), included into the educational process of the Preparatory Faculty (level A-2, B-1), for language acquisition speciality has been proposed. The article is based on the Prof. D. Izarenkov Scientific School concept. He proved that exercise apparatus combined a great number of exercises in a special system. Classification is based on the basis of 3 distinctive indications: operational content of the speech activity; unites of training; content of intellectual side of the speech activity in the process of doing exercises. This classification has some advantages in comparison with the others. It includes a great variety of exercises and remains at the same time an open system. It opens some possibilities to choice the necessary exercises in the frame of the method of teaching. System of exercises is represented in the form of exercise microsystem. Actuality and perspectives of the proposed selection and possibility to use it for creation of text-books for foreign students have been proved. System description of the exercise apparatus may be perspective for the researchers and for the teachers, who control practical work with the students. Descriptions of different teaching aids, proposed by different educational institutes, have been presented. Conclusions about using different classifications have been made. Authors believe, that traditional classifications can be used in the formation of exercises system in the work with different levels of students as well as post-graduate students. Different examples of text-books construction, using the existing exercise systems, have been also described.